Assessment of safety of masonry buildings near deep excavations: impact of excavations on structures - Jasiński, Radosław; Skrzypczak, Izabela; Leśniak, Agnieszka; Natividade, Eduardo (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
The knowledge of the impact and the load-bearing capacity of unstrengthened/strengthened structures is a crucial source of information about the safety of masonry buildings near deep excavations, especially in dense urban areas. Incorrect calculations made for such designs can seriously affect not only an analyzed object but also the adjacent buildings. The safety of masonry buildings can be determined by many factors that are closely related to the hazards presented during the performance of deep excavations. These factors are at first identified and then prioritized. The AHP process in the multi-criteria analysis was used to support the decision-making process related to the verification of factors affecting the safety assessment of masonry buildings in the area of deep excavations. The proper design of building structures, including the verification of the structure strengthening near deep excavations, was found to be the most significant factor determining the safety of such buildings. The methodology for proceeding with the verification of ultimate (ULS) and serviceability (SLS) limit states in accordance with the literature data, current regulations, such as Eurocode 6 and other design standards, and the know-how of the authors, described in this paper was the next stage of the discussed analysis.